UTILIZATION OF NON-HAZARDOUS SECONDARY SLUDGE FROM BEVERAGE INDUSTRY WWTP AS A COMPOST SUBSTITUTE IN PLANTING MEDIA - Mahendra, Bara; Warmadewanthi, I D A A; Nurhayati, Ervin; Bagastyo, Arseto Yekti (Purifikasi, 2025)
Secondary sludge generated from aerobic biological treatment in beverage industry wastewater plants is produced in large quantities and contains essential nutrients that offer potential for beneficial reuse. This study evaluates the utilization of non-hazardous secondary sludge as planting media by characterizing sludge properties and assessing its performance when mixed with three different type of soils (Soil A, B, and C) and amendments. Sludge cake was blended with each soil type as a control, and further treatments incorporated (a) dolomite, (b) Trichoderma sp., and (c) a combination of both amendments. The mixtures were monitored over two weeks for C/N ratio and N, P, K content, following compost quality parameters. Results indicate that most mixtures achieved a C/N ratio ≥10 after two weeks, except for Soil A with and without dolomite. All treatments exceeded the minimum compost nutrient requirements set by SNI 19-7030-2004. The application of Trichoderma sp. produced the highest nutrient enhancement, with nitrogen reaching 1.8% and phosphorus reaching 4.0% in sludge–Soil C mixtures, while potassium peaked at 0.4% in sludge–Soil B with Trichoderma sp. These findings confirm that secondary sludge from beverage industry WWTPs can be processed into viable planting media or compost substitutes, supporting sustainable sludge management and circular economy practices.